The Efficacy of Berberine-Containing Quadruple Therapy on Helicobacter Pylori Eradication in China: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Hu, Qian; Peng, Ze; Li, Lingli; Zou, Xin; Xu, Lijun; Gong, Jing; Yi, Ping (Frontiers in Pharmacology, 2020)
Background: Berberine-containing quadruple therapy (adding berberine to the standard triple therapy) is being used to treat Helicobacter pylori infection, but the effects in randomized controlled trials (RCTs) are still controversial. Therefore, a meta-analysis is needed to estimate the efficacy and safety of berberine-containing quadruple therapy on Helicobacter pylori eradication. Methods: Ten databases were searched to find the available literature. RCTs about the efficacy and safety of berberine-containing quadruple therapy on Helicobacter pylori eradication were included. The data of Helicobacter pylori eradication rate, peptic ulcer healing rate, relieving rate of clinical symptoms and adverse events were extracted to appraise the net change with a fixed or randomized effect model. Results: A total of 13 articles were included in the analysis. Pooled results showed that the addition of berberine in standard triple therapy significantly improved Helicobacter pylori eradication rate (RR 1.22; 95% CI 1.16 to 1.27; I2=12%), increased the peptic ulcer healing rate (RR 1.15; 95% CI 1.10 to 1.19; I2=44%), relieved the clinical symptoms (RR 1.11; 95% CI 1.06 to 1.17; I2=44%) and reduced the incidence of side events (RR 0.65; 95% CI 0.53 to 0.80; I2=58%) comparing to the standard triple therapy. Conclusions: The analysis showed that the addition of berberine in standard triple therapy could improve Helicobacter pylori eradication rate and clinical symptom remission rate, accelerate ulcer healing and reduce adverse events, which is very beneficial to clinical work in China.